1967
DOI: 10.1192/bjp.113.502.950
|View full text |Cite
|
Sign up to set email alerts
|

Chlorpromazine and the Untreated Chronic Schizophrenic: A Long-Term Trial

Abstract: Although chlorpromazine was the first of the phenothiazine drugs to be used in psychiatry, and has since been the subject of an extensive literature, there is a surprising dearth of information about the nature of its effect in chronic schizophrenia. Some early reports indicated that it produced a beneficial change, but before this could be examined and documented the attention of most psychiatrists was diverted to newer and supposedly more potent analogues. The present trial was undertaken with three factors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

1976
1976
2014
2014

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(12 citation statements)
references
References 6 publications
0
12
0
Order By: Relevance
“…Two used the toss of a coin [16,17], and 2 used random number tables [18,19]. Citations to all included and excluded studies are available in the full Cochrane Review [12], otherwise the names and dates cited in this text relate to Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Two used the toss of a coin [16,17], and 2 used random number tables [18,19]. Citations to all included and excluded studies are available in the full Cochrane Review [12], otherwise the names and dates cited in this text relate to Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…The symptoms targeted by medication include symptoms causing alienating behaviors such as hallucinations (positive symptoms), and symptoms such as apathy and social withdrawal (negative symptoms). However, it was soon discovered that negative symptoms were resistant to medication (Letemendia & Harris, ). Severe negative symptoms causing social withdrawal were observed to be endemic to this population.…”
Section: Theoretical Perspectivesmentioning
confidence: 99%
“…the majority of neuroleptics), as indicated above, produce no therapeutic effects in some schizophrenics, are probably not as effective for the majority of schizophrenics as was at one time thought, but may have some effect on non-schizophrenic symptoms. Indeed, responsiveness to phenothiazines has been suggested as a criterion over and above symptomatology for the subcategorization of schizophrenia (Letemendia & Harris, 1967). The discovery of elevated densities of dopamine D2 receptors in the caudate, putamens, nucleus accumbens and substantia nigra of some (for a period) neuroleptic-free schizophrenics does suggest that dopamine over-activity plays some role in some aspects of what is called schizophrenia (Owen, Owen, Poulter & Crow, 1984), although other studies have indicated that many of the observed dopamine abnormalities may be due to neuroleptic medication (Gattaz, 1983;Mackay, 1982).…”
Section: (Ii) Predictive Validitymentioning
confidence: 99%